Molecular markers in ovaries of female pigs with different levels of welfare, in the pre-mating period - Silva, Arthur Nery da (2021)
The role of the environment in the trajectory of individuals has been studied for hundreds of years. From the beginning of this research field, authors have been noticed that there was an intimate relationship between the environment that individuals live in and the way they express themselves phenotypically. In this study, we reviewed the current literature concerning epi-markers to predict welfare in pigs and conducted a novel study on the role of environmental experiences on genomic factors in the porcine corpus luteum. In the first study, we reviewed the evidence regarding the development of a panel of epigenetic indicators associated with the negative experiences that pigs may have undergone during their lifespan. In this review of evidence collected over the last 10 years, published in international peer-reviewed journals, we identified positive perspectives regarding the consistency of epigenetic markers in the genome of farm animals, which could predict their welfare. However, we also pointed out high variability concerning genes differentially affected by these markers, which can be explained by their high diversity in terms of the experimental context. In the second manuscript of this dissertation, we presented a novel study showing that a single dose of lipopolysaccharide (LPS) was capable of down-regulating gene expression of the angiogenic gene (VEGF) in the corpus luteum of gilts housed in different welfare conditions. This study simulates one of the biggest challenges of intensive pig farming: urinary tract infections by gram-negative bacteria, which have LPS in their external membrane wall. Overall, our study revealed important findings concerning environmental factors that can compromise the productive, reproductive, and welfare aspects of pigs. Furthermore, it is reasonable to say that other fields of study can benefit from our evidence since the porcine model is recognized as one of the best species for translational research.